2009
DOI: 10.4314/gjcm.v2i1-2.47923
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Patterns Of Salmonella Species In Contemporary Medical Practice: Challenges And Prospects In Treatment Of Enteric Fevers

Abstract: Treatment of enteric fever is increasingly becoming very challenging due to the increasing wave of antibiotic resistance. This study is a review of the contemporary antimicrobial susceptibility pattern of Salmonella species. The antimicrobial susceptibility pattern of Salmonella species to a wide range of antimicrobial agents was compiled for a period of 10 years (1997-2006). Data was obtained from published articles on both in vitro and in vivo susceptibility patterns of the organism to various drugs during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…to gentamycin without any resistance recorded. Notwithstanding, our study partly corroborates studies done by Jambo et al [22] who recorded a low 6.9% susceptibility to gentamycin with a 93.1% resistance to the antibiotics. Level of resistance against gentamycin was very much in agreement to the findings of Samanta et al [23] who found 100% of their Salmonella isolates resistant gentamycin in India.…”
Section: Resultssupporting
confidence: 92%
“…to gentamycin without any resistance recorded. Notwithstanding, our study partly corroborates studies done by Jambo et al [22] who recorded a low 6.9% susceptibility to gentamycin with a 93.1% resistance to the antibiotics. Level of resistance against gentamycin was very much in agreement to the findings of Samanta et al [23] who found 100% of their Salmonella isolates resistant gentamycin in India.…”
Section: Resultssupporting
confidence: 92%
“…to Gentamycin without any resistance recorded. Notwithstanding, our study corroborates with report by Jambo et al [29] who recorded a low 6.9% susceptibility to Gentamycin with a 93.1% resistance to the antibiotics. Level of resistance against Gentamycin was very much in agreement to the findings of Samantha et al [30] who found 100% of their Salmonella isolates resistant Gentamycin in india.…”
Section: Spp Count Of the Various Sample Parts From The Three Marketssupporting
confidence: 93%